THE RESULTS OF USING OF INDICATORS OF THE HIGH-TEST CAST IRON OF TYPE ICH STRUCTURE IN CONDITIONS OF PRODUCT - A. L. Majorov; A. R. Bajev; G. E. Konovalov; N. N. Gil (Литьë и металлургия)
The results of development of the indicator of highstrength pig-iron are submitted in the report. The indicator using allows to carry out the testing of the pig-iron structure in conditions of manufacture without additional preparation of the casting surface.